LAW REFORM OF SMALL AND MEDIUM ENTREPRISES (SMEs) AND EQUITABLE COOPERATIVE FOR COMPETITIVENESS IMPROVEMENT IN AEC ERA - Koesrianti, Koesrianti (Faculty of Law, Universitas Jenderal Soedirman, 2016)
Small Medium Entreprises (SMEs) and Cooperative have not received a proper law protection in facing trade liberation of ASEAN Economic Community (AEC) and economic globalized world. In 2015 AEC has been established that would bring a huge change in Southeast Asia regionS and definitely will have a wide impact to business people in Indonesia. SMEs and Cooperative contribute to more than 90 percent of total Indonesian national economy. However, they are weak on investment and information technology and management skill as well as competition law among ASEAN Member States. Economic policies do not give a sufficient protection to SMEs and Cooperative. This article tries to seek solutions for SMEs problems especially their legal structure in order to enhance their competitiveness. This article argues that the government can provide legal protection by reforming SMEs economic sectors similar to the AECâ€™s priority sectors by which the Indonesianâ€™ SMEs would become world class corporate.Â Keywords: Cooperative, AEC, legal reform, SMEs